﻿Evolution of connective glands reveals a new synapomorphy for Malpighiaceae and the hidden potential of staminal glands for Malpighiales systematics - Rafael Felipe de Almeida; Gustavo Arévalo-Rodrigues; Isa L. de Morais; Poliana Cardoso-Gustavson (PhytoKeys, 2023)
Connective glands are important morphological characters for the taxonomy of some genera of Malpighiaceae, with few recent studies having just elucidated these glands’ anatomical and ecological functions. In order to test the systematic relevance of connective glands to the currently accepted phylogenetic informal clades of Malpighiaceae, we characterised the anatomy and/or histochemistry of two-thirds of Malpighiaceae genera and ten species from nine families of Malpighiales to test: 1. Do connective glands occur in the flowers of all informal clades of Malpighiaceae?; and 2. Are they taxonomically relevant to characterise those clades? We sampled 25 genera and 26 species of Malpighiaceae, processing their anthers using traditional anatomical methods and characterising their glands using light microscopy and SEM imaging. Selected species were subjected to histochemical tests, and an additional 21 genera and 33 species of Malpighiaceae and nine families (ten species) of Malpighiales were included in our sampling from the literature. Three anatomical characters were scored, coded and mapped using Maximum Likelihood methods onto the molecular phylogeny of Malpighiaceae. All sampled species of Malpighiaceae showed connective glands characterised as epidermal or trichomal elaiophores. Our character-mapping analyses recovered connective elaiophores as a new synapomorphy for Malpighiaceae. Different types of epidermal or trichomal elaiophores were recovered as homoplasies for the Christianella and Banisteriopsis clades and the genera Byrsonima, Camarea and Cottsia. Our analyses also recovered the glands’ place of insertion in the stamen and the exudate type as potential new synapomorphies or homoplasies for the families of Malpighiales sampled. Our results propose the connective elaiophores as a new synapomorphy for Malpighiaceae and hypothesise the role that different staminal glands might play in the systematics of Malpighiales. Further comprehensive anatomical studies are still needed for the staminal glands of most families of this order to shed new light on the patterns recovered in our study.